Long‐term soy consumption and tumor tissue MicroRNA and gene expression in triple‐negative breast cancer. Issue 16 (16th May 2016) - Guo, Xingyi; Cai, Qiuyin; Bao, Pingping; Wu, Jie; Wen, Wanqing; Ye, Fei; Zheng, Wei; Zheng, Ying; Shu, Xiao‐Ou
Abstract : BACKGROUND: Soy food intake may have protective effects against the risk for breast cancer, including estrogen receptor (ER)–negative breast cancer. However, the underlying molecular mechanisms remain unclear. METHODS: To evaluate the association of soy intake with the expression of microRNAs (miRNAs) and genes in the tumor tissue of patients with triple‐negative breast cancer (TNBC; ie, breast cancer lacking expression of ER, progesterone receptor, and human epidermal growth factor receptor 2), the expression of 800 miRNAs and 302 genes were measured with NanoString nCounter assays in formalin‐fixed, paraffin‐embedded tumor tissue from 272 TNBC patients. Soy intake during the 1‐year period before the cancer diagnosis was assessed with a validated food‐frequency questionnaire. The association of soy intake with the expression of miRNAs and genes was evaluated via linear regression analysis with adjustments for patient age and TNM stage. RESULTS: A total of 14 miRNAs and 24 genes were significantly associated with soy food intake ( P < .05): Thirteen of the 14 miRNAs (92.9%) and 9 of the 24 genes (37.5%), including tumor suppressors miR‐29a‐3p and IGF1R, showed overexpression for those women with high soy intake, whereas the remaining miRNAs and genes, including oncogenes KRAS and FGFR4, showed underexpression. Furthermore, cell growth–related genes showed a predominantly underexpression pattern according to a comparison of tumor samples from women with high soy food intake and samples from women with lower soy food intake. CONCLUSIONS: This study suggests that long‐term prediagnosis soy intake may lead to increased expression of tumor suppressors and decreased expression of oncogenes, especially cell growth–related genes, in breast tumor tissues. Cancer 2016;122:2544–51 . © 2016 American Cancer Society . Abstract : Soy food consumption may influence the risk and prognosis of breast cancer by altering the expression of cancer‐related microRNAs and genes.